Surgical management of mesiodens based on characteristics and complications of the condition: a systematic review - Rahadian, Bayu; Julia, Vera; Sulistyani, Lilies D. (Journal of Stomatology, 2020)
Disturbances in dental development may result in anomalies, such as supernumerary teeth in the upper or lower jaw. Mesiodens is the most prevalent supernumerary tooth that is often found in the midline of the maxilla and can cause problems, such as malpositioned permanent teeth, diastema formation, cyst formation, and delayed eruption of maxillary anterior incisors. Surgical treatment might be an option for the management of this condition. This study aims to review the characteristics and complications, which need to be considered for the surgical management of mesiodens. A literature search for articles written in English and published within the last 10 years was conducted using the electronic database, PubMed. The keywords verified by Medical Subject Headings included mesiodens, characteristics, complications, and management. A total of 60 articles were retrieved; however, after exclusion, only 45 articles were relevant for evaluation. Subsequently, only 30 articles with full-text versions available online were included in the study. Based on this review, the majority of studies factored in the complications of mesiodens during treatment planning. Very few studies covered the relationship between the characteristics and complications of this condition and its management.